TANGGAPAN PENGUNJUNG PADA OBJEK WISATA AIR PANAS HAPANASAN KABUPATEN ROKAN HULU - Fia Aangraini; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the response of tourists to Hapanasan Hot Water, Rokan Hulu Regency and to know the tourist attraction of Hapanasan Hot Water in Rokan Hulu Regency. This study uses a quantitative method with a descriptive approach to describe and explain the situation that occurs by collecting data and information in the field. In this study, the data collection techniques used were observation, questionnaires and documentation. Based on the results of the questionnaire, it shows that the response of visitors to the Hapanasan Hot Spring Tourism Destination in Rokan Hulu Regency is good, where the concepts used are Destination Attractions, Destination Facilities, Accessibility, Image, and Price. The tourism response at Hapanasan Hot Spring in Rokan Hulu Regency in the sub-variable of destination attractions, destination facilities, accessibility is considered good by visitors who have visited Hapanasan Hot Springs, while for the Image sub-variable it is considered quite good by visitors who have visited Hot Water Hapanasan and the last is the price sub-variable which is considered poor by visitors who have visited Hapanasan Hot Spring.Key words : Responses, Visitors and Appeal